The role of nutrition in the prevention of childhood obesity: a systematic review - de Lacerda, Dhiego Alves; de Oliveira, Anaylle Vieira Lacerda; do Vale, Maria Eduarda Mulato; Celeste, Heitor Estrela; Cruz, Kayck Ryan Fernandes; Miranda, José Leonardo Frutuoso; Cavalcante, Ayla Alves; Neto, Valentim Fragoso de Freitas; Braga, Thárcio Ruston Oliveira (Revista Sistemática, 2024)
Childhood obesity is a globally recognized public health problem with significant long-term health consequences. Diet plays a key role in the development and prevention of childhood obesity. According to Rosenbaum et al. (2014), childhood obesity is associated with an increased risk of developing comorbidities such as type 2 diabetes and cardiovascular disease in adulthood. Therefore, it is essential to understand the relationship between nutrition and childhood obesity prevention in order to develop effective intervention strategies.